HUBUNGAN MINAT BELANJA GENERASI MILENIAL DAN GENERASI Z DI ERA DIGITAL - Meri Roito Siregar; Laisa Asri Nasution; Mawar Rasimah Br. Dalimunthe; Anggi Zahara Tarigan; Siti Suaibah Nasution (JURNAL ILMIAH NUSANTARA, 2025)
In the era of digitalization, payment methods are growing rapidly, especially in the shopping interest of Millennials and Generation Z is increasing, especially with the ease of access to information and products through social media, marketplaces, and other digital platforms, however, preferences for payment methods can vary depending on the factors that affect them. This study aims to analyze the relationship between Millennial and Generation Z spending interest in payment methods such as cash, debit, and QRIS. The study used a quantitative approach with survey techniques and interviews with 70 respondents in East Medan. The results show that Millennials tend to choose cash payments (57.1%), while Generation Z prefers digital methods, especially QRIS (47.1%). This analysis was assisted by using the Chi-Square test which showed a statistically significant relationship between generations and payment method preferences. The results of this study provide important input for business people and financial service providers in designing payment and marketing strategies that suit the characteristics of each generation.